SMALL AND MEDIUM SCALE BUSINESS FAILURE IN NIGERIA - Alo, Olubunmi Akinsanya; Olatunji, Kareem Alidu (IJRDO - Journal of Social Science and Humanities Research, 2018)
The developed and developing nations of the world are facing high rate of failures among smalland medium scale enterprises (SMESs). The experience of Nigeria is very pathetic as many ofthese businesses fail too often and many die in their infancy. Given the high failure rate of smalland medium scale enterprises internationally and locally, the objectives of this study are; toinvestigate the cases of failure among SMESs in Nigeria, to determine the influences of sociocultural factors on small and medium scale business failure in Nigeria and to ascertain measuresthat can ameliorate the failure rate of these businesses. Qualitative method is adopted in thisstudy through in-depth interview of owner-manager of fifty purposively selected SMESs andobservation of their transaction records, and the expansion of their workforce (employees) in thelast three years. Findings show that most of the small scale enterprises failed due to lack ofinfrastructural facilities and entrepreneurial skills, inadequate managerial skills, illiteracy,obsolete technology, insufficient finance, multiple taxations by different levels of government,neglect, fraud, corruption and natural disaster. Socio-cultural factors impacting negatively onbusiness failure are attitude, norms, values, religious belief and ostentatious life style of citizen. This study recommended adequate business planning, strategic implementation of procedures,training of owner-manager to acquire entrepreneurial skill, reduction of interest rates by financialinstitutions, provision of infrastructural facilities and human capital development. If thesemeasures are put in place SMESs will be able to play their role in the area of employmentgeneration, wealth creation, increasing standard of living of the citizenry and generate foreignexchange for the country to boast her Gross National Products and consequently achieveeconomic growth and sustainable development.